Temporal-aspectual values of the présent de l’indicatif in sports headlines in French-language newspapers - Quintero Ramírez, Sara (Lenguas Modernas, 2020)
In this article, we identify the temporal-aspectual values that the present indicative tense has in a corpus of 238 headlines of the sports section of five Frenchlanguage newspapers. The only characteristic in common in all our headlines is that they have at least one verb conjugated in present indicative tense. We decide to examine a corpus with these characteristics because this tense is commonly used in the newspaper headlines not only in French but also in Spanish and English (cf. Quintero Ramírez, 2017). Moreover, this particular tense allows a textual coherence between the headline and the body of the text, it does not matter in what tense the text is written. According to our observations of the corpus, the present indicative tense has temporal values of present, past and future. It also has aspectual values of perfectivity and imperfectivity. These values derive from the cotextual and contextual precisions in which the present indicative tense is used.